Defining Fast Fashion and Exploring Consumer Generated Metaphors around Fast Fashion. A ZMET Study - Tseng, YI-WEI (2016)
Nowadays, most customers are fashion-conscious and the successful business model of fast fashion has attracted considerable attention from both the academic field and business field. However, in the past, most research referred to fast fashion focused on a supply chain related perspective, studies on customer perspectives have been growing but it is still insufficient. Therefore, this paper intends to address this gap and with a study from a customer perspective. The purpose of this research is to explore the underlying thoughts of customers regarding fast fashion. The Zaltman Metaphor Elicitation Technique (ZMET) was selected to gain a better understanding of the responses from participants. The methodology was conducted in two interviews. A semi-structured interview was first conducted and an in-depth interview for the second time around. A total of 20 respondents were recruited; 10 from European countries and the other 10 respondents from Asian countries. The major findings from the study were divided into three themes; supply chain perspectives, sustainable perspectives and customer behaviour perspectives. As well as complementing existing literature, this research provides additional point of views on the existing model of supply chain, sustainability and customer bahaviour for the fast fashion industry.